Knowledge and practice of parents towards childhood immunization in Rompin, Pahang, Malaysia - Lee, Siew Pien; Mohd Arifin, Siti Roshaidai; Mohd Razali, Rossheilawanie; Makhzir, Norafisyah (2019)
Introduction: The childhood immunization can be considered as mortality prevention during the last decades particularly among children under 5 years of age. Parents’ knowledge and practices regarding immunization are likely to be a major factor that could contributed a successful immunization. As the primary health decision makers for their children, the knowledge and practice of parents towards immunization is a vital issue to improve the children health as well as prevention of disease. Objective: The objective of present study was to determine the knowledge, and practices of parents regarding childhood immunization. Material and Methods: The cross-sectional descriptive study was conducted among parents in Rompin, Pahang, Malaysia. A set of self-administered questionnaires that consist 20 questions was used to examine the level of knowledge and level of practice on childhood immunization among 153 parents. The descriptive analysis was shown percentages and frequencies. The association between the level of knowledge and practice on childhood immunization of parents was analysed using chi-square test, p<0.05 was considered as statistically significant. Results: Out of 153 parents surveyed, 82 (53.6%) parents have high level of knowledge and 111(72.5%) parents have a good practice on childhood immunization. There was a strong positive correlation between the knowledge and practice on childhood immunization among the parents (r = 0.841; p = 0.000). Conclusion: Although parents had adequate knowledge and practice on some aspects regarding childhood immunization, gaps were identified. There is a need for educational interventions to upgrade parents’ knowledge especially for resident of rural areas.